Assessing the Mediation Mechanism of Job Satisfaction and Organizational Commitment on Innovative Behavior: The Perspective of Psychological Capital - Tang, Yuan; Shao, Yun-Fei; Chen, Yi-Jun (Frontiers in Psychology, 2019)
Due to increasingly intense competition among companies, employees’ innovative behavior has not only become a crucial factor for company development but also a topic of broad and current interest among companies and researchers. It is a requisite for companies to identify the antecedents of employees’ innovative behavior. The main objective of this study was to investigate the effect of psychological capital (PsyCap) on employees’ innovative behavior through its relationship with job satisfaction and organizational commitment. The partial least squares method was adopted in this study to analyze 266 employees from China. The results showed that PsyCap had positive effects on job satisfaction and organizational commitment, and verified the relationship between employees’ innovative behavior and their job satisfaction and organizational commitment. Moreover, the mediating effect of PsyCap in terms of job satisfaction and organizational commitment on employees’ innovative behavior was verified by a mediation analysis. Employees’ innovative behavior is not only essential for the research and development department; rather, it is also important for other departments. The empirical results of this study show that companies should consider taking measures to increase employees’ PsyCap, so as to enhance their innovative behavior. Lastly, the study also provided the managerial implications of its findings and recommendations for future research.